Anne Frank: The Diary of a Young Girl - Frank, Anne 1929-1945 (Listening Library, 2010)
An adolescent Jewish girl chronicles her experiences over the years she and several others hid from the Nazis in a secret apartment before being discovered and sent to concentration camps. Includes entries previously omitted
Recommended for listeners ages 11 to 17
Keywords: Frank, Anne / 1929-1945 / Diaries; Holocaust, Jewish (1939-1945) / Netherlands / Amsterdam / Personal narratives; Jews / Persecutions / Netherlands / Amsterdam; Jews / Netherlands / Amsterdam / Diaries; Audiobooks; Amsterdam (Netherlands) / Ethnic relations; Jews / Persecutions / Netherlands; Holocaust, Jewish (1939-1945) / Amsterdam / Personal narratives; World War, 1939-1945 / Jews / Netherlands; Netherlands / History / German occupation, 1940-1945; Frank, Anne / 1929-1945; Holocaust, Jewish (1939-1945); Ethnic relations; Jews; Jews / Persecutions; Netherlands / Amsterdam; World War, 1939-1945 / Jews; Holocaust, 1939-1945 / Personal narratives; Netherlands / History / 1940-1945, German occupation; 1939-1945; Compact discs; Diaries; Personal narratives; Children's audiobooks; Hörbuch; Jugendbuch